Preservasi Pengetahuan Kegiatan Tamaik Kaji dalam Budaya Pernikahan di Kota Pariaman, Sumatera Barat - Hany Nandia Putri; Desriyeni Desriyeni (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2023)
This study aims to explain community knowledge, forms of knowledge preservation, and community participation in tamaik kaji activities in marriage culture in Pariaman City. This research is a type of qualitative research with an ethnographic approach. The research subjects were the administrators and members of the majelis taklim in Pariaman City, totaling three people. The research instruments used were interviews guidelines. Data collection techniques are participatory observation, interviews, and documentation. The validation test of the data in this study used technical triangulation and member checks. Data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that first, the people of Pariaman City who carry out tamaik kaji activities in marriage culture have good knowledge detailed information about these activities. The community knows clearly how this activity can become a traditional culture of marriage, and what is contained in it. Second, the knowledge preservation of tamaik kaji activities is seen by using the exchange of indigenous knowledge which consists of six aspects, namely recognizing and identifying, validating, recording and documenting, storing, transferring, and disseminating knowledge. Third, community participation in preserving tamaik kaji activities shows a decrease in enthusiasm and community participation in preserving these activities.